Induced Resistance by a Long-Chain Bacterial Volatile: Elicitation of Plant Systemic Defense by a C13 Volatile Produced by Paenibacillus polymyxa - Lee, Boyoung; Farag, Mohamed A.; Park, Hyo Bee; Kloepper, Joseph W.; Lee, Soo Hyun; Ryu, Choong-Min (PloS one, 2012)
Some strains of plant growth-promoting rhizobacteria (PGPR) elicit induced systemic resistance (ISR) by emission of volatile organic compounds (VOCs) including short chain alcohols, acetoin, and 2,3-butanediol. The objective of this study was to evaluate whether species-specific VOCs from PGPR strain Paenibacillus polymyxa E681 can promote growth and induce resistance in Arabidopsis. The efficacy of induction was strain-specific, with stronger protection against Pseudomonas syringae pv. maculicola ES4326 in plants exposed to VOCs from P. polymyxa E681 versus Arabidopsis plants exposed to VOCs from a reference strain Bacillus subtilis GB03, which was previously shown to elicit ISR and plant growth promotion. VOC emissions released from E681 primed transcriptional expression of the salicylic acid, jasmonic acid, and ethylene signaling marker genes PR1, ChiB, and VSP2, respectively. In addition, strain E681 produced more than thirty low molecular-weight VOCs, of which tridecane was only produced by E681 and not found in GB03 or IN937a volatile blends. These strain-specific VOCs induced PR1 and VSP2 genes. These results provide new insight into the existence of a long chain VOC signaling molecule produced by P. polymyxa that can serve as a bacterial trigger of induced systemic resistance in planta.